Menakar Efektivitas Politik Hukum Perdagangan Dalam Menopang Kemandirian UMKM Di Indonesia - Sunanda, Erwin; Fatimah, Siti; Irwan, Irwan; Alfarisi, Muhammad Adib; Mulyadi, Ardian (Universitas Cokroaminoto Yogyakarta, 2025)
Analyzing the effectiveness of trade legal politics in supporting the independence of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through the implementation of Law Number 20 of 2008. MSMEs are a strategic sector that plays a vital role in the national economy but still face various challenges such as limited access to capital, markets, technology, and adequate legal protection. This study employs a normative-empirical approach with literature and policy document analysis, based on Soerjono Soekanto’s theory of legal effectiveness and Mahfud MD’s theory of legal politics. The findings indicate that although the regulation provides a strong legal framework for MSME development, its implementation remains less than effective due to complex bureaucracy, low digital literacy, and lack of institutional synergy. This study recommends the need for more adaptive policy reform, bureaucratic simplification, enhanced institutional synergy, and capacity building for MSMEs through training and the utilization of information technology.